Input variability and late acquisition: clitic misplacement in European Portuguese - Costa, João (2016)
This paper reports a study on the acquisition of clitic placement by European Portuguese children aged 5, 6 and 7, using an elicitation task. Contrarily to what has been found for other languages, where children correctly place clitic pronouns from a very early age, our results show that European Portuguese children still misplace clitics at age 7, although there is a developmental effect from 5 to 7: they overuse enclisis in proclisis contexts, but not the other way round. This confirms previous studies based on spontaneous production. Our study shows, however, that: i) the rates of clitic misplacement are not identical in all proclisis contexts; ii) proclisis is acquired earlier in some contexts; iii) the contexts that are harder to acquire are the ones where we find more variability in the adult control group, and where diachronic data are not so categorical. We argue that, since clitic placement in European Portuguese is not linked to the finite/non finite distinction, there is a slower developmental path, reflecting the complexity of the input and the specific properties of lexical items and syntactic contexts.